Teachers perception on the level of school culture among secondary schools - Dahiru, Abbas Sani; Lope Pihie, Zaidatol Akmaliah (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
The purpose of this study was to determine the level of school culture among secondary schools in Zamfara State, Nigeria. 358 teachers participated in the study. Survey method was employed in collecting the data, and the data were analyzed using descriptive statistics. The findings show that the level of school culture was at a moderate level, in addition market culture type recorded highest mean score, however adhocracy culture was found to have, and lowest mean score. Furthermore, market culture was found to be the culture type with the highest mean score, while adhocracy culture was found to have the lowest mean score. The implication of findings is that, there is the need for the policy makers and school leaders to evolve ways of improving school culture to the highest level for the attainment of an effective teaching and learning process.